Partnership in the primary school : working in collaboration - Mills, Jean, 1947- (Routledge, 2002)
Working in 'partnership' in primary schools is an approach that is transforming the classrooms of the 1990s. It is now widely acknowledged that a collaborative approach can significantly improve the effectiveness of teaching. This book provides a practical, readable account of partnerships in educational settings including: * collaborating in nurseries and primary schools * reading and literacy partnerships * working with special needs assistants * supporting students in training * home-school links * liaising with an OFSTED inspector. The focus is placed on key. -- Provided by publisher.
Keywords: Teaching teams -- Great Britain.; Group work in education -- Great Britain.; Elementary school teaching -- Great Britain.; Enseignement -- Travail en équipe -- Grande-Bretagne.; Enseignement primaire -- Grande-Bretagne.; EDUCATION -- Elementary.; Elementary school teaching; Group work in education; Teaching teams; Great Britain